Asuhan Kebidanan Continuity Of Care (COC) Pada Ibu Hamil, Bersalin, Nifas, Bbl Dan Keluarga Berencana Pada Ny. A Di Klinik Pratama Kita Kecamatan Sei Bingai Kapupaten Langkat - Thoibah; Rapika Duri; Siti Hawa Manau; Robina Novalince Tambunan; Mardiati; Ribur Sinaga; Situmorang, Khairunnisa (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
Based on the latest Indonesian Demographic and Health Survey (IDHS) in 2018, Indonesia's Maternal Mortality Rate (MMR) is 359 per 100,000 live births, while the Infant Mortality Rate (IMR) is 40 per 1,000 live births. The purpose of this study was to provide comprehensive midwifery care from pregnancy, childbirth, newborn care (BBL), postpartum and family planning using a midwifery management approach in the form of SOAP. This research is a type of research used is descriptive with a case study approach. In this case study, the author takes the subject of Mrs. A with Continuity of care (CoC) from pregnancy to family planning at the Pratama Kita Clinic in 2021. After carrying out a case study of continuous care (COC) on Mrs. D from pregnancy to postpartum and family planning and BBL care, where Mrs. D's pregnancy is a physiological pregnancy, Mrs. D's delivery is spontaneous vaginally. Mrs. A's involution postpartum period was normal, Mrs. D's baby was normal, there was an increase in weight according to age, there was no infection in the umbilical cord and the baby was exclusively breastfeeding, postpartum family planning, Mrs. D and her husband chose MAL, so it is known that sustainable care is effective in preventing both morbidity and mortality. It is recommended to the Pratama Kita Clinic to maintain the quality of midwifery services or care for pregnant women, maternity, newborns, and perform midwifery care in accordance with existing theories.